Community opinion on the personal brand of Bobby Nasution to Prospective Medan Mayor in 2020 - Panjaitan, Fathur Rahman; Harahap, Muhammad Said (COMMICAST, 2021)
The current phenomenon in the world of politics is flooded with families of politicians who run for politics. Where the next cabinet will be dominated by young people. On the other hand, a young politician, although included in the scope of a political dynasty, shows that young people are not politically apathetic. And to continue to exist in the world of politics, personal branding is needed where every candidate for politicians must build a name or reputation which means creating a "brand" or public perception of them. Bobby Nasution as one of the candidates for the mayor of Medan 2020 tries to create positive personal branding among the people of Medan. This study aims to determine how the public opinion on the personal brand of the 2020 Medan Mayor Candidates. This type of research uses quantitative descriptive research. The population in this study were the people of Tanjung Selamat Subdistrict, Medan Tuntung District, with 100 people as the sample in the study. Data collection techniques in this study were observations and questionnaires (questionnaires). Data analysis in this research is a single table analysis. This research was conducted in the environment III Tanjung Selamat, Medan Tuntung District. When this research was conducted in July 2020. The results of the study, namely personal branding, aim to obtain perceptions that give rise to a positive reputation for the individual. But in fact, the personal brand Bobby Nasution tends to be less than optimal in the Tanjung Selamat Community. This research concludes that Bobby Nasution's brand as a candidate for Mayor of Medan in 2020 raises public opinion and raises the pros and cons of society.